Proconosama takiyae, a new sharpshooter from Ecuador, the female of P. alalia (Distant), and a key to the species of the genus (Hemiptera: Cicadellidae: Cicadellinae: Proconiini) - Mejdalani, G.; Cavichioli, R. R.; Carvalho, R. A. (Zootaxa, 2012)
Proconosama takiyae sp. nov. is described and illustrated from Ecuador. The new taxon can be distinguished from the other six known species of Proconosama Young, 1968 by the following combination of features: (1) pronotum with a large transverse yellow macula; (2) forewings with a large yellow macula on the basal portion of clavus; (3) male pygofer processes extremely elongate, slender, their inferior portions curved medially and crossing each other below the aedeagus; (4) preatrium of aedeagus with a pair of conspicuous sclerites directed dorsally; (5) aedeagal shaft extremely small compared to the size of the atrium. The female of Proconosama alalia (Distant, 1908) is described and illustrated based on material from Peru. This is the first detailed description of the genitalia of a female Proconosama. A preliminary key to the species (males) of the genus is provided.